Does the objective measurement of muscle strength improve the detection of postoperative residual muscle weakness? - Durga Padmaja; Geetha Singam; Rabbani Tappa; Krishnarao Maremanda; Nitesh Kabra; Anupama Barada (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: The postoperative residual neuromuscular block (PRNB) has a significant impact on patient safety and well-being, but continues to remain underestimated. Objective evaluation of handgrip strength using a force dynamometer can be useful to identify postoperative muscle weakness. Material and Methods: Thirty-two American Society of Anesthesiologists (ASA) class I and II patients who received general anesthesia were included. Patients were extubated after the train-of-four (TOR) ratio (TOFR) was >0.90 and the clinical criteria for motor power recovery were judged as adequate. The measurements of handgrip strength and peak expiratory flow rate (PEFR) were obtained at baseline, 15 min after extubation, and 1, 2, and 4 h postoperatively. The incidence of significant decline from baseline (>25%) was determined. The correlation between handgrip strength and PEFR was assessed using Spearman correlation. The time to return to baseline for muscle grip strength and PEFR was performed using Kaplan–Meier survival analysis. A P value of 0.05 was considered significant for all tests. Results: The incidence of the significant decline in handgrip strength from baseline was 100% at 15 and 60 min, 76% at 2 h, and 9.4% at 4 h. There was a strong correlation between muscle grip strength and PEFR (0.89, P < 0.001). None of the patients exhibited the potential complications of PRNB. (PRMB in abstract. It should be uniform) The mean time to return to the baseline value of muscle grip strength was 3.8 h (95% confidence interval [CI] 3.6–3.9), and the mean time to return to baseline for PEFR was 3.2 h (95% CI 2.9–3.4 h). Conclusion: Objective assessment of muscle grip strength using a force dynamometer has the potential to be a new objective metric to monitor postoperative muscle weakness.